Grid Forming Control for Power Converters Based on an Inertial Phase Locked Loop (IPLL) - Andres Tarraso; Jose Ignacio Candela; Joan Rocabert; Zoran Miletic; Alvaro Luna (IEEE Access, 2023)
Inertia emulation is claimed to play a decisive role in the regulation and management of frequency in modern electrical systems. The support offered by renewable energy power plants and distributed generators is key to diminish the rate of change of frequency (RoCoF), as many synchronous generators are being replaced all around the globe. It is a reality that the implementation of the swing equation in the power converter control has been the core of several proposals on grid-forming controllers to emulate inertia. This kind of controller has been heavily studied and integrated in some demonstrators around the world during the last years, providing dynamic inertia support functionalities. However, the need to modify the synchronization strategy in already deployed power units has been one of the key opposition factors on industry, leading to a severe shortcoming on the integration. In contrast to the traditional swing equation implementation this paper presents a lightweight inertial phase-locked loop (IPLL) able to take the most of inertial features introducing minor changes on classical power converter control and synchronization structures. As shown in this work, the straightforward implementation significantly reduces the technological and computational effort compared to other synchronous emulation proposals. Moreover, it integrates not only dynamic inertial response to the converter, but also all grid-forming capacities to the power conversion unit. This modification on the synchronization structure enables the converter to work in grid-following mode in grid-tied applications, and grid-forming in islanded ones. The integration of the proposed IPLL, the stability analysis and a sample of its performance in HIL and experimental environments will be presented in this paper.